(untitled) (AmS-Varia, 2020)
This article discusses how to better unlock the information potential of unremarkable, though complex, prehistoric stone-built structures, by integrating the past 30 years worth of Nordic archaeological research results into aspects of the Norwegian Cultural Heritage Management processes. Traditionally, it has been rather commonplace to interpret such manmade collections of rocks as remains of either clearance of fields for agricultural purposes or as containers for burials, but this dichotomy should now be regarded as an oversimplification. The site of Orstad in the county of Rogaland, SW Norway, excavated in 2014, serves as a case study. This paper demonstrates how difficult it can be to put updated theories and methods into proper use in the field. Since these new research results call for changes in the approach to the subject were not sufficiently considered in the planning process, neither time nor budget allowed for an adequate examination of the individual structures and their context. This is likely to cause information loss, which creates challenges for both the excavation and post-excavation phases of an archaeological investigation. This paper stresses the need to update and improve how excavations of such sites are handled within Norwegian cultural heritage management. By applying new approaches, such localities can yield more information about the past than previously assumed.